Myonecrosis by Clostridium septicum in a dog, diagnosed by a new multiplex-PCR - Ribeiro, Márcio Garcia [UNESP]; Silveira Silva, Rodrigo Otavio; Pires, Prhiscylla Sadana; Vitirito Martinho, Anna Paula [UNESP]; Lucas, Thays Mizuki [UNESP]; Passarela Teixeira, Ana Izabel; Paes, Antonio Carlos [UNESP]; Barros, Claudenice Batista [UNESP]; Faria Lobato, Francisco Carlos (Elsevier B.V., 2012)
Clostridial myositis is an acute, generally fatal toxemia that is considered to be rare in pet animals. The present report describes an unusual canine clostridial myositis that was diagnosed by a new multiplex-PCR (mPCR) designed for simultaneous identification of Clostridium sordellii, Clostridium septicum, Clostridium perfringens type A, Clostridium chauvoei, and Clostridium novyi type A. A ten-month-old male Rottweiler dog, that had displayed lameness and swelling of the left limb for 12 h, was admitted to a veterinary hospital. The animal was weak, dyspneic and hyperthermic, and a clinical examination indicated the presence of gas and edema in the limb. Despite emergency treatment, the animal died in only a few minutes. Samples of muscular tissue from the necrotic area were aseptically collected and plated onto defibrinated sheep blood agar (5%) in anaerobic conditions. Colonies suggestive of Clostridium spp. were submitted to testing by multiplex-PCR. Impression smears of the tissues, visualized with Gram and also with panoptic stains, revealed long rod-shaped organisms, and specimens also tested positive using the fluorescent antibody technique (FAT). The FAT and mPCR tests enabled a diagnosis of C. septicum myonecrosis in the dog. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Clostridium septicum; Gas gangrene; Canine